Evaluation of the Implementation of Pharmaceutical Service Standards at the Keerom District Health Center, Indonesia - Imba, Farhan; Wiwin Herdwiani; Tri Wijayanti (Open Access Indonesian Journal of Medical Reviews, 2024)
Pharmaceutical services are an integral part of health services that focus on optimizing drug use to achieve optimal therapeutic results. Regulation of the Minister of Health of the Republic of Indonesia Number 73 of 2016 concerning Pharmaceutical Service Standards at Health Centers is a reference in providing quality pharmaceutical services. This study aims to evaluate the implementation of pharmaceutical service standards at the Keerom District Health Center. This research uses a descriptive method. Data was collected through questionnaires and observation sheets at 6 Health Centers in Keerom District. Data were analyzed using SPSS to calculate percentages and average values. The research results show that the level of implementation of pharmaceutical service standards at the Keerom District Health Center is in the good category with an average value of 78-84%. The categories with the highest scores are the pharmaceutical preparation management category (84%) and the drug information services category (82%). The category with the lowest score is the quality assurance category (78%). In conclusion, the overall implementation of pharmaceutical service standards at the Keerom District Health Center has reached the good category. Improvement efforts need to be made in several categories, such as quality assurance, to achieve optimal pharmaceutical services.